GDP-L-fucose is required for boundary definition in plants. (25th November 2017) - Gonçalves, Beatriz; Maugarny-Calès, Aude; Adroher, Bernard; Cortizo, Millán; Borrega, Nero; Blein, Thomas; Hasson, Alice; Gineau, Emilie; Mouille, Grégory; Laufs, Patrick; Arnaud, Nicolas
Abstract : Mutation of MURUS1 suppresses the highly serrated leaf phenotype that results from overexpression of CUP-SHAPED COTYLEDON 2 in Arabidopsis, revealing that GDP-L-fucose is involved in defining tissue boundaries during plant development. Abstract: The CUP-SHAPED COTYLEDON (CUC) transcription factors control plant boundary formation, thus allowing the emergence of novel growth axes. While the developmental roles of the CUC genes in different organs and across species are well characterized, upstream and downstream events that contribute to their function are still poorly understood. To identify new players in this network, we performed a suppressor screen of CUC2g-m4, a line overexpressing CUC2 that has highly serrated leaves. We identified a mutation that simplifies leaf shape and affects MURUS1 ( MUR1 ), which is responsible for GDP-L-fucose production. Using detailed morphometric analysis, we show that GDP-L-fucose has an essential role in leaf shape acquisition by sustaining differential growth at the leaf margins. Accordingly, reduced CUC2 expression levels are observed in mur1 leaves. Furthermore, genetic analyses reveal a conserved role for GDP-L-fucose in different developmental contexts where it contributes to organ separation in the same pathway as CUC2. Taken together, our results reveal that GDP-L-fucose is necessary for proper establishment of boundary domains in various developmental contexts.